Arrested development: misguided directions in deterrence theory and policy - Pickett, Justin T. (Criminology & public policy, 2016)
Deterrence theory assumes that objective and subjective sanction risk are positively related. If this assumption holds true, then the theory is useful for guiding criminal justice policy and practice. However, prior research has failed to support the assumption. Prominent review articles have dismissed this literature on the basis of methodological critiques, and they have presented certain requirements for future deterrence research to be considered credible. Informed by these reviews, Nagin, Solow, and Lum's (NSL, 2015) new deterrence theory of policing rests on the assumption of a strong positive relationship between objective and subjective sanction risk. NSL have asserted that their theory has significant policy implications; indeed, they have contended it reveals a need to alter American policing fundamentally. We elaborate why the critiques of the discredited literature are premature, and we suggest that the plausibility of NSL's theory is called into question by this literature, as well as by other logical inconsistencies. We conclude by emphasizing how much remains unknown about sanction perception updating, hot spots policing, and heuristics and biases in offender decision making.